Comparison Between Powered and Manual Toothbrushes Effectiveness for Maintaining an Optimal Oral Health Status - Yeh CH; Lin CH; Ma TL; Peng TY; Vo TTT; Lin WN; Chen YH; Lee IT (Dove Medical Press, 2024)
Chin-Hsuan Yeh,1,* Chia-Hsuan Lin,2,* Tien-Li Ma,3 Tzu-Yu Peng,4 Thi Thuy Tien Vo,5 Wei-Ning Lin,6 Yu-Hsu Chen,7,8 I-Ta Lee4 1Division of Oral and Maxillofacial Surgery, Department of Dentistry, Taipei Medical University Hospital, Taipei, Taiwan; 2Department of Family Medicine, Taoyuan General Hospital, Ministry of Health and Welfare, Taoyuan, Taiwan; 3School of Dental Technology, College of Oral Medicine, Taipei Medical University, Taipei, Taiwan; 4School of Dentistry, College of Oral Medicine, Taipei Medical University, Taipei, Taiwan; 5Faculty of Dentistry, Nguyen Tat Thanh University, Ho Chi Minh City, 700000, Vietnam; 6Graduate Institute of Biomedical and Pharmaceutical Science, Fu Jen Catholic University, New Taipei City, Taiwan; 7Department of Orthopedic Surgery, Taoyuan General Hospital, Ministry of Health and Welfare, Taoyuan, Taiwan; 8Department of Biology and Anatomy, National Defense Medical Center, Taipei, Taiwan*These authors contributed equally to this workCorrespondence: I-Ta Lee, School of Dentistry, College of Oral Medicine, Taipei Medical University, Taipei, Taiwan, 250 Wuxing St, Taipei, 11031, Taiwan, Tel +886-2-27361661 ext. 5162, Fax +886-2-27362295, Email itlee0128@tmu.edu.twAbstract: This integrative literature review evaluates the effectiveness of power toothbrushes (PTBs) compared to manual toothbrushes (MTBs) across various populations, focusing on plaque removal, gingival health, calculus reduction, and stain removal. PTBs equipped with advanced technologies such as oscillating-rotating and high-frequency sonic mechanisms have been examined for their potential to enhance oral hygiene. Special attention is given to vulnerable groups, including the elderly and individuals with intellectual disabilities, to assess how PTBs meet their specific oral health needs. A comprehensive literature search was conducted in databases including PubMed, Cochrane Library, Embase, and Google Scholar using keywords such as "power toothbrush", "electric toothbrush", "manual toothbrush", "plaque removal", "gingivitis", "calculus", "dental stains", "oral hygiene", "elderly", and "intellectual disabilities". Studies published between 2000 and 2024 were selected based on their relevance to the PTB and MTB comparison, with an emphasis on outcomes related to oral hygiene efficacy. As this review is narrative rather than systematic, it focuses on synthesizing existing knowledge without applying strict inclusion or exclusion criteria. The results indicate that PTBs generally outperform MTBs in reducing plaque, gingivitis, and stains, though the benefits for special populations are less pronounced but still significant. However, practical issues such as user experience and mechanical reliability of PTBs warrant further investigation. In conclusion, this review enhances the understanding of PTB effectiveness, guides consumer choices, and informs future technological advancements in dental care practices.Keywords: power toothbrushes, manual toothbrushes, plaque removal, gingival health, dental calculus, oral hygiene